Rehabilitation using virtual reality technology: a bibliometric analysis, 1996–2015 - Huang, Youliang; Huang, Qian; Ali, Sajid; Zhai, Xing; Bi, Xiaoming; Liu, Renquan (Scientometrics, 2016)
The aim of this study is to conduct a retrospective bibliometric analysis of articles about rehabilitation medicine using virtual reality technology. Bibliometrics is one subfield of scientometric. It is an effective tool for evaluating research trends in different science fields. A systematic bibliometric search was performed using three academic databases (PubMed, Scopus and Web of Science) between January 1, 1996, and December 31, 2015. Research outputs, countries, institutions, authors, major journals, cited articles, subject area and hot research topics were analyzed to base on bibliometrics methodologies. The retrieval of results was analyzed and described in the form of texts, tables, and graphics. Total of 15,191 articles were identified from three academic databases; and from them 48.32 % published as original articles. The articles were originated from 101 countries and territories. United States was ranked first with 4522 articles, and United Kingdom was on second with 1369 articles. 96.75 % of the articles are published in English. 527 articles were published by the Lecture Notes In Computer Science Including Subseries Lecture Notes In Artificial Intelligence And Lecture Notes In Bioinformatics. With regard of the research institutions, Eidgenossische Technische Hochschule Zurich published 208 articles ranked first. In the past 20 years, the research outcome of rehabilitation using virtual reality technology research has increased substantially. This study provides a valuable reference for researchers to understand the overview and present situations in this field.